A 30-year mortality and respiratory morbidity study of refractory ceramic fiber workers. (24th August 2017) - LeMasters, Grace; Lockey, James E.; Hilbert, Timothy J.; Levin, Linda S.; Burkle, Jeff W.; Shipley, Ralph; Perme, Charles; Meyer, Cristopher A.; Rice, Carol H.
Abstract: Aim: Report mortality ( n  = 1119), cancer incidence ( n  = 1207) and radiographic ( n  = 1451) findings from a 30-year investigation of current and former refractory ceramic fiber (RCF) workers. Methods: Cause of death, health and work histories, radiographs and spirometry were collected. Mortality and cancer incidence were analyzed. Logistic regression analysis investigated the associations of latency and cumulative fiber exposure (CFE) on radiographic changes. Results: The mortality study showed no increase in standardized mortality rates (SMR) for lung cancer, but urinary cancers were significantly elevated in the higher exposed group (SMR = 3.62, 95% CI: 1.33–7.88) and leukemia in the total cohort (SMR = 2.51, 95% CI: 1.08–4.94). One death attributed to mesothelioma was identified (SMR = 2.86, 95% CI: 0.07–15.93) in a worker reporting some asbestos exposure. The overall rate of pleural changes was 6.1%, attaining 21.4% in the highest CFE category for all subjects (adjusted odds ratio (aOR) = 6.9, 95% CI: 3.6–13.4), and 13.0% for those with no reported asbestos exposure (OR= 9.1, 95% CI: 2.5–33.6). Prevalence for recent hires (≥1985) was similar to the background. Interstitial changes were not elevated. Localized pleural thickening was associated with small decreases in spirometry results. Conclusion: Increases in leukemia and urinary cancer but not lung cancer mortality were found. One death attributed to mesothelioma was observed in a worker with self-reported asbestos exposure and a work history where occupational asbestos exposure may have occurred, rendering uncertainties in assigning causation. Radiographic analyses indicated RCF exposure alone is associated with increased pleural but not interstitial changes. Reductions in RCF exposure should continue. The mortality study is ongoing.